Recentralization of Regional Authority: Legal Implications of the Enactment of Emergency Law Number 2 of 2022 on Job Creation in Regional Autonomy - Maulidi, Mohammad Agus (Universitas Islam Negeri Raden Intan Lampung, 2023)
The Enactment of Emergency Law Number 2 of 2022 on Job Creation(Job Creation Emergency Law) brings significant juridical implications to the implementation of decentralisation in Indonesia. This research aims to analyse the form of recentralization policy in the Job Creation Emergency Law and the implications of the recentralization policy in the Job Creation Emergency Law on the implementation of regional autonomy in Indonesia. Employing a normative juridical research method, and conceptual and statutory approaches, this research concludes: firstly, there are at least three forms of recentralisation following this Emergency Law, including health policy based on Law Number 36 of 2009 concerning Health, repositioning of the status and relation of the central and regional governments related to the role of regional governments in implementing or establishing legislation which should be interpreted as the execution of presidential authority, and the centralisation of business licencing that shifts the mechanism and system of business licences to the centre; secondly, the emergency Law Number 2 of 2022 on Job Creation threatens the success of the implementation of regional autonomy. The success of regional autonomy, which can be measured by the independence of the regions in the sense of reduced dependency on the central government and the ability of the regions to enhance their economic capabilities, is increasingly jeopardised by the Job Creation Emergency Law, which substantially contains recentralization policy. However, in the context of business licencing, there exists an anomaly in the form of eased licencing expected by centralising the system and mechanisms, thus opening the tap to investment, which in turn will boost not only the national economy but also the economies of the regions where the businesses operate